Convergent Light Volumes for Indirect Illumination - BRATTÉN, JAKOB; LINDÉN, DANIEL (My University, 2014)
This thesis examines a technique to approximate indirect illumination in real time on modern computer hardware. Incoming light information is stored in a regular grid, called a light volume, by rasterizing large quantities of line segments into a 3D texture. Since indirect illumination is generally quite consistent between frames, several light volumes can be merged to achieve more stable lighting. In order to allow fast changes of the indirect illumination from fast moving light sources, each cell in the light volume can be weighted differently when they are merged. Since all of the light information is stored in a grid, dynamic as well as static objects can be lit using the same technique which ensures consistent lighting.
Keywords: Data- och informationsvetenskap; Computer and Information Science